Klausula Novasi Dalam Perjanjian Kredit Dengan Jaminan Hak Tanggungan - Widhiyanti, Hanif Nur; Suhariningsih; Arini (Fakultas Hukum Universitas Airlangga, 2024)
AbstractNovation is one method of breaking an agreement. Novation is not effectively governed in Article 1413 of the Civil Code, the Banking Law, or the Mortgage Law. Therefore, it is frequently observed in practice that novations are carried out unilaterally by creditors and without the original debtor’s involvement (passive subjective novation). When the Novation is implemented for the Credit Agreement and is also weighed down by Mortgage Rights, issues arise. The legal relationship between the Creditor and the original Debtor will be terminated when the Debtor is renewed. Between new Debtors and existing Creditors, Novation creates a new legal relationship. Only if there has been an engagement between himself and the original Debtor would the new Debtor have the right to the guarantee of Mortgage. Novation can be one of the exit strategies for avoiding the possibility of bad loans, but particularly for Credit Agreements that are Mortgage-burdened, it is necessary to use the principle of prudence, which includes the urgency of having a companion deed as well as other administrative procedures, so that the existence of Mortgage can still be a “safety measure” for the agreement for the renewed credit.Keywords: Novation; Bank Credit Agreement; Land Mortgage; Notary. AbstrakSalah satu cara mengakhiri perikatan adalah Novasi. Di dalam Pasal 1413 KUHPerdata, Undang-Undang Perbankan dan Undang-Undang Hak Tanggungan, Novasi tidak diatur secara. Oleh karena itu, di dalam praktek banyak ditemui Novasi dilakukan secara sepihak oleh Kreditur dan tanpa melibatkan Debitur lama (Novasi Subyektif Pasif). Permasalahan muncul ketika Novasi tersebut dilakukan untuk Perjanjian Kredit dibebani pula Hak Tanggungan. Bahwa adanya pembaharuan Debitur, maka hubungan hukum antara Kreditur dengan Debitur lama menjadi terhapus. Novasi menghadirkan hubungan hukum baru antara Kreditur dengan Debitur baru. Dalam kaitannya dengan jaminan Hak Tanggungan, maka Debitur baru hanya akan mempunyai hak, jikalau telah terjadi perikatan antara dirinya dengan Debitur lama. Novasi dapat menjadi salah satu exit strategy dalam mengatasi kemungkinan kredit macet, namun khususnya untuk Perjanjian Kredit yang dibebani Hak Tanggungan, perlu asas kehati-hatian termasuk urgensi adanya akta pendamping dan juga proses administrasi lainnya sehingga keberadaan Hak Tanggungan tetap dapat menjadi “pengaman” atas perjanjian kredit yang diperbaharui tersebut.Kata Kunci: Novasi; Perjanjian Kredit Perbankan; Hak Tanggungan Atas Tanah; Notaris.